Finansowanie działalności zakładów ubezpieczeń - Chmielowiec-Lewczuk, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The financing insurance companies activity bases on two sources: capital and technical reserves. In article is presented short description of character Polish insurance companies in context of their capital structure. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 106-112